2017
DOI: 10.1111/jsap.12686
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of refractory sino‐nasal aspergillosis with posaconazole and terbinafine in 10 dogs

Abstract: The results of this study suggest that this combination therapy appears safe and well-tolerated for the treatment of refractory sino-nasal aspergillosis in dogs. Long-term survival is possible with prolonged treatment, but relapse is possible. Larger prospective studies are warranted to further evaluate these preliminary findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…29 Additionally, the safety of combined posaconazole and terbinafine therapy has recently been reported in a clinical study. 28 The skin lesions responded well to this therapy; however, it did not prevent the development of further, although milder, lesions when immunosuppressive treatment with prednisolone was reintroduced. This again highlights the importance of tapering of immune-suppressive therapy for the successful management of deep mycoses.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…29 Additionally, the safety of combined posaconazole and terbinafine therapy has recently been reported in a clinical study. 28 The skin lesions responded well to this therapy; however, it did not prevent the development of further, although milder, lesions when immunosuppressive treatment with prednisolone was reintroduced. This again highlights the importance of tapering of immune-suppressive therapy for the successful management of deep mycoses.…”
Section: Discussionmentioning
confidence: 93%
“…A previous in vitro study reported the combination of terbinafine with second‐generation azoles reduced the MIC of both drugs against P lilacinus isolates 29. Additionally, the safety of combined posaconazole and terbinafine therapy has recently been reported in a clinical study 28. The skin lesions responded well to this therapy; however, it did not prevent the development of further, although milder, lesions when immunosuppressive treatment with prednisolone was reintroduced.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Oral treatments with antifungal drugs (azole derivatives) have generally poor to moderate efficacy, require prolonged administration and are commonly associated with adverse effects (Peeters & Clercx ). However, improved clinical remission rates were recently reported for combination treatment with posaconazole and terbinafine (Stewart & Bianco ). Treatment with enilconazole or clotrimazole infusion administered topically through catheters placed surgically, blindly or endoscopically have been associated with higher success rates (Peeters & Clercx , Billen & Peeters ).…”
Section: Introductionmentioning
confidence: 99%